Laser Beam Soldering of Fine Pitch Technology Packages with Solid Solder Deposits. - Pucher, Hans-Jörg; Glasmacher, Matthias; Geiger, Manfred (Proceedings of the OE/LASER Optoelectronics and Lasers, 1996)
Micro electronics is a key technology attracting the attention of information, communication, automation and data processing technologies. Ongoing miniaturization combined with an increasing number of I/Os has inevitably lead to ever finer lead geometries. Therefore the demands put upon the surface mount technology are increasing continuously. Processing of high lead count fine pitch packages, for example those which are applied in high-capacity computers, has not increased the demands put upon the assembly process only, but also on the connecting techniques. By reflow soldering with laser beam radiation the benefits from the tool 'laser beam' are used extensively, for example contact and force free processing, strictly localized heating and the good controllability thereof, formation of fine crystalline and homogeneous structures, etc. Within the scope of this paper the fundamentals of laser beam soldering are discussed for fine pitch lead frames (pitch 300 micrometers ) for plastic packages, made by a modified CuFe2P alloy with a 5 micrometers Sn90Pb plating, on solid solder depths (Sn63Pb) performed by the so called High-Pad process. These investigations are unique in the field of laser beam soldering and are carried out by means of a Nd:YAG-laser. A pyrometer is used for detection of the emission of the temperature radiation of the joining area for process control. The additional use of a high-speed camera gives a detailed description of the melting and wetting process. The influence of laser beam parameters and the volume of the solid solder deposits on the joining result are presented. ©2005 Copyright SPIE - The International Society for Optical Engineering.
LFT Import::2019-08-05 (668)
Keywords: Electronics production; Fine pitch technology packages; Laser beam soldering; Reflow soldering and wetting process; Solid solder deposits